2016
DOI: 10.1002/cpdd.279
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Polyglutamate Monitoring in Patients With Crohn's Disease

Abstract: Methotrexate is an efficacious immunosuppressant for induction and maintenance of remission in Crohn's disease. The goal of this pilot study was to determine whether total or individual methotrexate glutamate levels (MTXGlu ) in red blood cells correlate with disease activity and adverse events in Crohn's disease. A cross-sectional study was undertaken with 12 patients on a stable dose of 25 mg weekly methotrexate (oral or subcutaneous). Clinical disease activity was assessed by the Harvey-Bradshaw Index (HBI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Both patients with CD and ulcerative colitis were enrolled, except in the study by Fischer et al . [ 18 ] The mean MTX-PG total concentration (140 ± SD 77 nmol/L) and inter-patient variability (CVs 27.2 to 103.5%) in our study was comparable with the data from most other studies, except for the study by Fischer et al . (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both patients with CD and ulcerative colitis were enrolled, except in the study by Fischer et al . [ 18 ] The mean MTX-PG total concentration (140 ± SD 77 nmol/L) and inter-patient variability (CVs 27.2 to 103.5%) in our study was comparable with the data from most other studies, except for the study by Fischer et al . (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In our population, MTX-PG n and MTX-PG total concentration were not associated with either disease activity at baseline ( p > 0.05) or disease activity at one year (data not shown). All previous studies measuring MTX-PG concentrations in patients with IBD did draw conclusions on the association of MTX-PG with disease activity, despite their cross-sectional study design [ 17 , 18 , 20 ]. Of note, the majority of studies included both CD and ulcerative colitis (UC) patients, and patients on concomitant TNF-α inhibitors, which impedes meaningful analysis of drug efficacy [ 17 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies ( n = 5) used ultra‐performance LC–tandem mass spectrometry (MS/MS), of which 2 studies used a stable‐isotope‐labelled internal standard 12,13 . Three studies reported drug levels in nmol/8 × 10 12 RBCs 44–46 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of MTX-Glu n in IBD are sparse and limited to adult observational studies smaller than ours, which may explain why prior studies also failed to demonstrate a statistically significant association between MTX-Glu n and IBD treatment response. [ 17 , 18 ]. In a cross-sectional study of 12 adults, Fischer et al observed higher long-chain MTX-Glu 3–5 in patients with Crohn’s disease in remission vs. active disease, but the trend did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of 12 adults, Fischer et al observed higher long-chain MTX-Glu 3–5 in patients with Crohn’s disease in remission vs. active disease, but the trend did not reach statistical significance. [ 17 ] Brooks et al found long-chain MTX-Glu 4–5 to correlate inversely with MTX efficacy in 18 adults with Crohn’s disease, with higher levels noted in patients experiencing gastrointestinal adverse effects [ 18 ]. However, findings of an inverse relationship between MTX-Glu n and MTX efficacy are not substantiated in most rheumatology literature [ 5 , 6 , 7 ], except for one study that found a positive correlation for MTX-Glu n with MTX dose, but a negative correlation with treatment outcomes in RA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%